Coherent diffraction imaging - Muhammad Khairul Ismail (2016)
CDI recovers the object’s image from its diffraction pattern by some phase retrieval methods. This project consists of both software and hardware work. On one hand, numerical simulations of CDI including phase retrieval will be carried out to understand the imaging process. On the other hand, experimental work would be conducted to verify the results obtained. Laser light from the source would be used to illuminate an aperture with micron size diameter in order to generate the diffraction pattern. This pattern will be captured using camera by conducting two different experiments with different problem solving methods. It will then be compared with the simulation reconstruction to distinguish the better methods.